Penguatan Keterampilan Konseling Anak: Memahami Karakteristik Anak melalui Permainan Balogo - mufida istati (Tarbiyah : Jurnal Ilmiah Kependidikan, 2017)
The aim of this study to know about Balogo game can help the counselor to understanding the children characteristics. This research is a qualitative study of literature study. In collecting the data, the writer used documentation. Data were analysis by Balogo game analysis from the theory psychology of childrent development by Nurihsan & Agustin (2011) and the theory children counseling by Geldard & Geldard (2012). The age of childrent in this research is 7-12 years old who get study in elementary school or Islamic elementary school. The children development characteristic can to know by the counselor through balogo game include the aspects of cognitive development, affective, physical-motor, moral, and religion. Counselors who understand the characteristics of children will support the achievement of child counseling success.